Occurrence and distribution of perfluoroalkyl substances (PFASs) in the water dissolved phase and suspended particulate matter of the Dalian Bay, China. (June 2018) - Ding, Guanghui; Xue, Huanhuan; Yao, Ziwei; Wang, Ying; Ge, Linke; Zhang, Jing; Cui, Fuxu
Abstract: In the present study, the contamination level and spatial distribution of PFASs in the water dissolved phase and suspended particulate matter (SPM) phase of the Dalian Bay, and the SPM-water partition behavior were investigated. The total concentrations of PFASs (∑PFASs) in the water dissolved phase ranged from 6.9 to 17.1 ng L −1, with perfluorooctanoic acid (PFOA), perfluorobutanoic acid, and perfluorobutane sulfonate (PFBS) as the predominant PFASs, while ∑PFASs in SPM ranged from 1.7 to 27.5 ng g −1 dw with higher contributions from PFBS, perfluorooctane sulfonic acid and PFOA. As for the pollution distribution, the concentrations of PFASs inside the Dalian Bay were higher than those outside the bay. For perfluoroalkyl carboxylic acid (PFCAs) and perfluoroalkane sulfonic acids (PFSAs), the suspended particulate matter-water partition coefficient (log K d ) values ranged from 2.62 to 3.76, and from 3.39 to 3.56, respectively. The log K d values of PFASs generally increased with the increasing perfluorinated carbon chain length. Short-chain PFCAs were mostly detected in the water dissolved phase, while long-chain PFCAs and PFSAs appeared to bind more strongly to SPM phase. The contamination level of long-chain PFCAs and PFSAs could be underestimated if only the water dissolved phase were measured. Therefore, further investigations should consider the role of SPM on the environmental behavior and fate of PFASs in the aquatic environment. Highlights: ∑PFASs in water phase and SPM ranged from 6.9 to 17.1 ng L −1 and 1.7–27.5 ng g −1 dw, respectively. The concentrations of PFASs inside Dalian Bay were higher than those outside the bay. The log K d of PFASs increased with the increasing perfluorinated carbon chain length. Short-chain PFASs are mostly presented in the water phase, while long-chain PFASs prevailed in SPM.